ANALISIS PENGENDALIAN SOSIAL PELANGGARAN TATA TERIB SEKOLAH DI SMA KARYA SEKADAU - Watini, Oktavianti Ardio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research entitled social control of school rules violation in SMA KaryaSekadau. The problem of this research is: how is the social control of school rules violation in SMA KaryaSekadau. The sub-problems in this research are: 1) How is the form of preventive social control and 2)How is the form of repressive social control. The research aims to analyze the social control preventively and repressively of school rules violation in SMA KaryakaryaSekadau. Research form used was qualitative with descriptive method. Data informant were: 1) The principal, Drs. Sumardi, 2) Vice Principal on Student Sector, Yasinta Yuyun, S.Sos, 3) Counseling Teacher, Lasna, S.Pd, 4) Homeroom Teacher Maria Mardiana, S.Pd, 5) Subject Teacher Fransiska, S.Pd, 6) supervisor in-charge when the observation was being held, Lita Lia, S.Pd. The result proved that there was a serious or well function social control which was controlled by the school i.e. the principal, vice principal on student sector, counseling teacher, homeroom teacher, supervisor in-charge, and subject teacher. Efforts or steps had been done to overcome school rules violation were by giving advice such as giving guidance and guiding the problematic students and giving warning such as directly reprimanding the students.Key words: Analysis, Social Control, Violation, School Rules